Immune-Effector Pathways Leading To Peanut-Induced Anaphylaxis - Arias, Katherine (My University, 2011)
Among food allergies, peanut has attracted the most research attention because the allergy is typically lifelong, often severe and potentially fatal. Furthermore, other than epinephrine, there are no treatments available to date. A decade of research has provided a great deal of insight into the factors that promote and regulate the development of allergic responses. However, less in known about the factors involved in the elicitation of the most common and severe manifestation of peanut allergy, namely anaphylaxis. The research in this thesis centers on the investigation of cellular and molecular pathways leading to peanut-induced anaphylaxis (PIA) as well as potential therapeutic targets. Specifically presented are: i) the development and characterization of a mouse model of PIA (Chapter 2), ii) the role of molecules including histamine, leukotrienes (LT) and platelet-activating factor (PAF) (Chapter 3) and, iii) the relative contribution of mast cells, basophils and macrophages as well as IgE and IgG1 (Chapter 4). Our data show that oral sensitization to peanut in C57BL/6 mice generated local and systemic markers of type-2 immunity that was associated with robust and consistent clinical anaphylaxis following antigen challenge. In this context, concurrent blockade of PAF and histamine receptors markedly decreases the severity of these reactions. Moreover, they demonstrate that distinctive immune effector pathways involving activation of mast cells (via IgE and IgG1) and macrophages (via IgG1) cooperate to elicit a broad range of systemic reactions to peanut. These findings highlight that concomitant and progressive recruitment of immune-effector pathways leads to a full range of anaphylactic reactions and therefore, therapeutic strategies for PIA may need to target several pathways or, alternatively shared components within these pathways. Combination therapy blocking both PAF and histamine may represent such as a therapeutic approach.
Keywords: Food allergy; Mast Cells; Platelet-activating Factor; IgE; IgG; Macrophages; Allergy and Immunology; Medical Immunology; Allergy and Immunology